The Evolution of Energy Market and Energy Usage: An Application of the Distribution Dynamics Analysis - Yigang Wei; Yigang Wei; Kenneth Hoi Ki Chung; Tsun Se Cheong; David Kam Hung Chui (Frontiers in Energy Research, 2020)
There has been a general consensus that greenhouse gas emission is closely related with energy consumption. A systematic and complete investigation of the state and evolution of the energy consumption structure (ECS) of global countries is of great importance to figure out the different positions, responsibilities and missions of each country in the global climate change cooperation. Furthermore, such task is of great policy implications to generate a global reference system for different countries, guiding each one to improve, update and optimize its ECS. However, most existing studies regarding the world ECS neglects the evolutionary trends of ECS and their distributional positions in the global picture. Noting the paucity of studies of convergence in ECS across the world countries, this paper aims to explore the evolution of ECS at the national level and the global level to sharpen understandings on the state of global energy transition by employing the distribution dynamics approach. Three major energy sources were investigated, including coal, oil, and natural gas. The dataset was collected from the Global Trade Analysis Project database whose latest version covers the period from 2004 to 2014. In the second part of the analysis, the dataset is further divided into different income groups so as to evaluate the impacts of income on the distribution dynamics. A distribution dynamics approach is used to analyze the data of almost all the countries and regions in the world. The visualization of global ECS provides an insightful and novel understanding on the underlying trends. This study fills an important gap in the literature by providing several important findings which are not available from traditional econometric techniques. First, many countries would reduce their relative coal and oil consumption in the future but oil would remain to be the most common form of energy source. However, great variability can be observed for the distribution of gas consumption. Second, from the ergodic distribution of the gas market, it can be observed convergence clubs may emerge in the long run as the countries would congregate in certain clusters with similar levels of gas consumption. These findings call for further research and policy planning for the development of gas industry. Third, the distribution dynamics is very different for the four income groups (according to the World Bank), and so it is necessary to take a country's income level into consideration in formulating energy policies. Fourth, our findings reflect the issue of global inequality amongst the countries as the energy consumption of the poor countries are much lower than the other countries. Fifth, oil is deemed to be the most popular form of energy sources for the upper-middle-income and high-income countries, while coal is not a preferred energy source for the affluent countries, thereby suggesting the need to provide aid to the poor countries for mitigating the use of coal. Finally, gas consumption seems to have a very high variability and the countries can have very different consumption patterns of gas even if they belong to the same income category, implying that country-specific policies should be formulated for the development of the gas industry. Furthermore, it is observed that for the lower-middle-income and upper-middle-income countries, the big consumers of gas tend to increase their gas consumption further. The findings derived from this study may prove valuable for the policy makers in formulating energy policies for adapting to market changes, and may assist the design of international aid program on mitigating carbon emissions for the poor countries.